Adaptation of problem-solving therapy for primary care to prevent late-life depression in Goa, India: the 'DIL' intervention. Issue 1 (1st January 2019) - Dias, Amit; Azariah, Fredric; Sequeira, Miriam; Krishna, Revathi; Morse, Jennifer Q.; Cohen, Alex; Cuijpers, Pim; Anderson, Stewart; Patel, Vikram; Reynolds, Charles F.
ABSTRACT: Background : Depression in late life is a major, yet unrecognized public health problem in low- and middle-income countries (LMICs). The dearth of specialist resources, together with the limited ability of current depression treatments to avert years lived with disability, underscores the need for preventive interventions that can be delivered by lay health workers in primary care settings. We describe the development of an intervention for the indicated prevention of depression in older adults at risk due to subsyndromal symptoms, attending rural and urban public primary care clinics in Goa, India. Objectives : (1) to describe a mixed-methods approach (qualitative and quantitative)to the development of 'DIL, ' an intervention for preventing the onset of major depression in older adults living with subsyndromal symptoms in Goa, India; (2) to describe resulting components of the 'DIL' intervention; and (3) to present data on the feasibility, acceptability, and benefit of DIL to participants. Methods : We followed a mixed-methods design, including in-depth interviews, focus group discussions, a theory of change workshop to develop a logic model, and an open-case series. Results : The mixed-method approach led to the development and adaptation of the DIL (Depression in Later Life) intervention for the indicated prevention of depression in older adults. The intervention was delivered by lay health counselors (LHCs). 'DIL' is a hybrid model of simple behavioral strategies grounded in Problem-solving Therapy for Primary Care, improved self-management of common, co-occurring medical disorders such as diabetes mellitus, and pragmatic assistance in navigating to needed social services. The use of 'DIL' in an open-case series with 19 participants led to a moderate reduction in symptoms of depression and anxiety on the General Health Questionnaire. A pictorial flipchart was developed to assist in delivering the intervention to participants with low levels of literacy. High rates of participant retention and satisfaction were achieved. Conclusion : The DIL intervention was adapted to the local context for delivery by lay health counselors and was found to be acceptable and feasible among the elderly participants in the study.